TINGKAT PARTISIPASI MASYARAKAT DALAM PERENCANAAN PEMBANGUNAN DESA ULIDANG KECAMATAN TAMMERODO KABUPATEN MAJENE - Herman, Herman (LPPM Universitas Muhammadiyah Mamuju, 2019)
Village development plays an important role because it is an inseparable part of regional and national development. In the governance structure, the village occupies the lowest position, but instead it is in the forefront and directly in the middle of the community. Therefore, it can be ensured that any form of development program from the government will always lead to the village. Community participation is an initiative and self-help that is a characteristic of the personality of the Indonesian nation. Initiative which means will, desire for desire, while self-help is mutual cooperation which means ability, kinship, so it needs to be organized